Here and there: the double-side transgene localization - P. A. Salnikov; A. A. Khabarova; G. S. Koksharova; R. V. Mungalov; P. S. Belokopytova; I. E. Pristyazhnuk; A. R. Nurislamov; P. Somatich; M. M. Gridina; V. S. Fishman (Вавиловский журнал генетики и селекции, 2021)
Random transgene integration is a powerful tool for developing new genome-wide screening approaches. These techniques have already been used for functional gene annotation by transposon-insertion sequencing, for identification of transcription factor binding sites and regulatory sequences, and for dissecting chromatin position effects. Precise localization of transgenes and accurate artifact filtration are essential for this type of method. To date, many mapping assays have been developed, including Inverse-PCR, TLA, LAM-PCR, and splinkerette PCR. However, none of them is able to ensure localization of both transgene’s flanking regions simultaneously, which would be necessary for some applications. Here we proposed a cheap and simple NGS-based approach that overcomes this limitation. The developed assay requires using intentionally designed vectors that lack recognition sites of one or a set of restriction enzymes used for DNA fragmentation. By looping and sequencing these DNA fragments, we obtain special data that allows us to link the two flanking regions of the transposon. This can be useful for precise insertion mapping and for screening approaches in the field of chromosome engineering, where chromosomal recombination events between transgenes occur in a cell population. To demonstrate the method’s feasibility, we applied it for mapping SB transposon integration in the human HAP1 cell line. Our technique allowed us to efficiently localize genomic transposon integrations, which was confirmed via PCR analysis. For practical application of this approach, we proposed a set of recommendations and a normalization strategy. The developed method can be used for multiplex transgene localization and detection of rearrangements between them.